Revolutionizing Self-Healing Asphalt: Optimized Encapsulated Rejuvenators for Enhanced Durability and Sustainability - Al-Khafaji, Fatimah Fahem; Hashim, Tameem Mohammed (Civil Engineering Journal, 2025)
In an era where sustainable infrastructure is crucial, self-healing asphalt emerges as a transformative solution to enhance pavement longevity and reduce maintenance costs, addressing the global challenge of deteriorating road networks. This study presents a pioneering investigation into the development and performance evaluation of encapsulated rejuvenators for self-healing asphalt, utilizing two distinct compositions; waste cooking oil (WCO) and Fischer-Tropsch bright stock oil (FTBSO), across three capsule sizes (1 mm, 2 mm, and 3 mm). Through the experimental tests on compressive strength, thermal stability, and rupture resistance under wet conditions, the ongoing study highlights the critical influence of capsule size and composition on the mechanical performance, as well as the resistance to degradation and oxidation under similar asphalt production conditions, including applied stresses and temperatures. The findings indicate the superior performance of 3 mm FTBSO-based encapsulated rejuvenators, which exhibit exceptional compressive strength (155 N), minimal weight loss (2% at 200° C after 1-hour short-term aging), and high rupture resistance (80 minutes to break under moisture at 100° C), making these capsules ideal for withstanding mechanical and thermal stresses, while ensuring effective crack repair. In addition, both 2 mm and 3 mm FTBSO- and WCO-based rejuvenator capsules demonstrated high resistance to compressive stresses, excellent thermal stability, and strong rupture resistance, making these capsules suitable for self-healing asphalt applications. In contrast, 1 mm WCO-based rejuvenator capsules exhibited the lowest compressive strength (32 N), the highest weight loss (10% after 1 hour of short-term aging at 200° C), and the fastest rupture under moisture (18 minutes to break at 100° C), making these capsules the least suitable for self-healing asphalt applications.